Smith predictor design by CDM for temperature control system - Roengruen, P.; Tipsuwanporn, V.; Puawade, P.; Numsomran, A. (My University, 2009)
Smith Predictor control is theoretically a good solution to the problem of controlling the time delay systems. However, it seldom gets use because it is almost impossible to find out a precise mathematical model of the practical system and very sensitive to uncertain system with variable time-delay. In this paper is concerned with a design method of smith predictor for temperature control system by Coefficient Diagram Method (CDM). The simulation results show that the control system with smith predictor design by CDM is stable and robust whilst giving the desired time domain system performance.
Keywords: CDM; Smith predictor; Temperature process